How do Fish Adapt to Extreme Environments? - Hennigh, Sam; Hallaq, Tom (Kansas State University, 2017)
Extreme environments allow for the investigation of life’s capacity and limitations to cope with far-from-average environmental conditions. Springs rich in hydrogen sulfide (H2S) represent some of the most extreme freshwater environments, because H2S halts energy production in animal cells. Nonetheless, some fish have colonized sulfide springs throughout the Americas, and it remains unknown how they can tolerate conditions so toxic that most other organisms perish. This project compares closely related populations that live in adjacent sulfidic or nonsulfidic habitats to identify differences in genetic, biochemical, and physiological traits that underlie tolerance to H2S. It involves the identification of genetic differences between H2S-tolerant and susceptible populations, particularly in genes associated with pathways affected by H2S toxicity or involved in H2S detoxification.
Keywords: Tobler, Michi